In–situ quantification of mechanical and permeability properties on outcrop analogues of offshore fractured and weathered crystalline basement: Examples from the Rolvsnes granodiorite, Bømlo, Norway. (February 2021) - Ceccato, Alberto; Viola, Giulio; Tartaglia, Giulia; Antonellini, Marco
Abstract: Fractured and weathered crystalline basement units below erosional unconformities potentially represent unconventional reservoirs for georesources (oil, mineral and water). The reservoir properties and characteristics strongly depend on secondary processes connected to the local structural and alteration/weathering history. Here we present the results of in–situ field quantification of mechanical (uniaxial compressive strength) and petrophysical (permeability) properties of a fractured and weathered crystalline basement at selected outcrops on the island of Bømlo (western Norway). The Bømlo outcrops are believed to represent an onshore analogue of the unconventional oil reservoir hosted in the offshore Utsira High granodioritic fractured basement (northern North Sea). The off– and onshore crystalline basements have both undergone surficial weathering during the Mesozoic, as shown by the occurrence of a dated, variably thick saprolitic profile on top of fresh fractured basement blocks. The Bømlo crystalline basement is characterized by a complex and highly permeable fracture network. Fault rocks within its fault zones are characterised by an anisotropic mechanical strength and by an average permeability that is two orders of magnitude larger than that of the host rock. The matrix permeability and mechanical strength are significantly affected by alteration/weathering products. Analysis of the textural and mineralogical characteristics of the weathered outcrops allowed us to constrain the variation of permeability and mechanical strength as a function of increasing alteration and to infer their distribution in the, now eroded, top–basement weathering profile on Bømlo. Weathering enhances permeability and drastically decreases the mechanical strength. Nevertheless, evolved saprolitic horizons may act as low–permeability top–seal units to the fractured and weathered crystalline basement reservoir. The obtained permeability and mechanical data are finally used to better constrain the potential reservoir rocks, the fluid migration pathways, and to discuss their role in the geomechanics of a conceptualised fractured and weathered crystalline basement unconventional reservoir. Highlights: Fracturing and weathering control reservoir properties in crystalline basements. Fracture and fault zones dramatically increase the host rock permeability. Brittle fault rocks are two orders of magnitude more permeable than the host rock. Weathering products are up to four orders of magnitude more permeable than the host rock. Fracturing and weathering create a significant mechanical heterogeneity in the reservoir.